Hailey-Hailey disease associated with herpetic eczema—the value of the Tzanck smear test - Thomás de Aquino Paulo Filho (Mattioli1885, 2014)
Background: Herpetic eczema is a herpetic superinfection of a preexisting skin disease. Hailey-Hailey disease is an autosomal dominant dermatosis that is clinically characterized by flaccid vesicles and rashes in intertriginous areas. The coexistence of those findings is a rare condition; only five cases have been published in literature.